Divergence Times and Phylogenetic Patterns of Sebacinales, a Highly Diverse and Widespread Fungal Lineage - Garnica, Sigisfredo; Riess, Kai; Schön, Max E.; Oberwinkler, Franz; Setaro, Sabrina D. (PLOS ONE, 2016)
Patterns of geographic distribution and composition of fungal communities are still poorly understood. Widespread occurrence in terrestrial ecosystems and the unique richness of interactions of Sebacinales with plants make them a target group to study evolutionary events in the light of nutritional lifestyle. We inferred diversity patterns, phylogenetic structures and divergence times of Sebacinales with respect to their nutritional lifestyles by integrating data from fossil-calibrated phylogenetic analyses. Relaxed molecular clock analyses indicated that Sebacinales originated late Permian within Basidiomycota, and their split into Sebacinaceae and Serendipitaceae nom. prov. likely occurred during the late Jurassic and the early Cretaceous, coinciding with major diversifications of land plants. In Sebacinaceae, diversification of species with ectomycorrhizal lifestyle presumably started during the Paleocene. Lineage radiations of the core group of ericoid and cavendishioid mycorrhizal Sebacinales started probably in the Eocene, coinciding with diversification events of their hosts. The diversification of Sebacinales with jungermannioid interactions started during the Oligocene, and occurred much later than the diversification of their hosts. Sebacinales communities associated either with ectomycorrhizal plants, achlorophyllous orchids, ericoid and cavendishioid Ericaceae or liverworts were phylogenetically clustered and globally distributed. Major Sebacinales lineage diversifications started after the continents had drifted apart. We also briefly discuss dispersal patterns of extant Sebacinales.